Interventions to reduce dietary salt intake in the out-of-home food sector: a systematic review - Victoria Olubunmi Olarewaju; Yee-How Say; Yook-Chin Chia (Discover Public Health)
Abstract Reliance on food and beverages prepared out-of-home (OOH) has increased in popularity. Excessive salt intake negatively impacts health, yet strategies to reduce salt in food prepared OOH have not been sufficiently addressed. This review aimed to characterise interventions targeting a reduction in salt intake and blood pressure in the OOH food sectors. Searches were conducted in PubMed, Cochrane Library, Google Scholar, Scopus, and EMBASE databases, resulting in the inclusion of 15 studies (four RCTs, five NRCTs, two cross-sectional studies, a comparative audit, and three studies with a pre-post design). There was the consistent use of multifaceted strategies, including nutrition education and training, menu or recipe reformulation, nutrition labeling, environmental modification, and the innovative use of dosage equipment. Overall, all reviewed interventions led to effective salt reduction post-study, without negatively affecting consumer acceptance of food, and resulted in improvements in participants’ blood pressure. The mean change in salt intake was significant in all studies except two. There were significant gaps in the geographical distribution of interventions, and none addressed the informal OOH sector, which encompasses street food vendors, market stalls, and food delivery services. The reviewed intervention results underscore the feasibility and potential of these salt reduction strategies. Also, they highlight the need for increased research resource mobilization, stricter enforcement of nutrition labeling legislations, continuous education and awareness efforts, intersectoral and multisectoral collaborations, and integration of ongoing monitoring and evaluation structures beyond the lifecycles of salt reduction projects OOH.